Analysis of Good Faith in Subsidized Property Disputes; A Case Study of Delayed Housing Handover by Developers - Marchelia, Andria; Miarsa, Fajar Rachmad Dwi (Ipso Jure, 2025)
Subsidized housing programs are designed to ensure access to adequate housing for low-income communities. However, delays in the delivery of houses by developers frequently occur despite buyers having fulfilled their contractual obligations. Such disputes are not merely cases of breach of contract but also involve the principle of good faith in contract performance. This study analyzes the meaning and function of good faith in disputes concerning delayed delivery of subsidized housing and examines the implications of normative ambiguity on consumer legal protection. Using a normative juridical method with statutory, conceptual, and case approaches, the study finds that the absence of operational standards of good faith in the Civil Code and housing regulations leads to legal uncertainty and inconsistent judicial reasoning. Delays by developers are not consistently considered violations of good faith, thereby weakening consumer protection. The study concludes that explicit normative indicators of developers’ good faith and regulatory harmonization are essential to ensure legal certainty and substantive justice.